The potential effect of offering lump sums as retirement payments - Raimond Maurer; Olivia S. Mitchell; Ralph Rogalla; Tatjana Schimetschek (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
The paper discusses an additional reform proposal for enhancing Social Security solvency which reframes the existing debate in a different light. In our research, we focus on incentives to prolong working years and to delay benefits claiming as a way of sustaining Social Security. Specifically, we analyze how the offer of a budget-neutral, actuarially fair lump sum payment - instead of the current delayed retirement credit - would encourage people to delay claiming their OASI benefits and work longer. The results of our research will be useful for policymakers, namely in (1) measuring who would delay claiming benefits if offered a lump sum instead of higher annuity payments, (2) examining how long they would wait, and (3) how much longer, if at all, they would continue working in the interim.
urn:nbn:de:hebis:30:3-390657
Keywords: 330; pension system; social security solvency